(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The present article investigates the theoretical foundations and pedagogical implications of habit formation in foreign language learning, drawing on behavioral psychology and the habit theory popularized in James Clear’s Atomic Habits. Although habit-based learning strategies are widely acknowledged as effective tools for developing sustainable learning behaviors, students frequently experience difficulties in applying these principles in academic contexts. The article analyzes the cognitive and environmental mechanisms underlying habit formation, identifies the main barriers faced by learners, and proposes a pedagogically adapted model for language acquisition. By integrating habit theory with established principles of educational psychology and second language acquisition, the study demonstrates that systematic, incremental, and environmentally supported habits significantly enhance learners’ consistency, motivation, and long-term academic performance.